the effect of ethanol on the level of sialic acid in the brain - Baghdad Science Journal (مجلة بغداد للعلوم)
The study dosage ethanol in the total content of acid sialic TC and acid sialic associated fat (LBSA) in blood serum and congener brain Dkor Jerd eggs study included dosage 20 animals of male rat Ald ethanol daily for a period of four weeks and concentrations 20% and 30%, 40%, 50% and size of dose 5mlThe results of the study showed that levels of TSA homogeneous in the brain and blood serum significantly reduced Ankhvaza